Economic History and Economics - Solow, Robert M. (American Economic Review, 1985)
I have in the back of my mind a picture of the sort of discipline economics ought to be -or at least the sort of discipline I wish it were. If economics were practiced in that way there would be nothing problematical about its reciprocal relationship with economic history. It would be pretty clear what it is that economic theory offers to economic history and what economic history offers to economic theory. I will try to describe what I mean below. For better or worse, however, economics has gone down a different path, not the one I have in mind. One consequence, not the most important one, but the one that matters for this discussion, is that economic theory learns nothing from economic history, and economic history is as much corrupted as enriched by economic theory. I will come to that, too, later on. You will notice that I am using strong language. I am prepared to admit right away that I may be dead wrong in my judgements. But there is no point in pussyfooting. Bluntness may lead to an interesting discussion. After all, no one would remember the old German Historical School if it were not for the famous Methodenstreit. Actually, no one remembers them anyway. (There must be a lesson in that.) To get right down to it, I suspect that the attempt to construct economics as an axiomatically based hard science is doomed to fail. There are many partially overlapping reasons for believing this; but since that is not the topic under discussion today, I do not have to lay them out in an orderly way. I hope the following hodgepodge will convey what I mean. A modern economy is a very complicated system. Since we cannot conduct controlled experiments on its smaller parts, or even observe them in isolation, the classical hardscience devices for discriminating between competing hypotheses are closed to us. The main alternative device is the statistical analysis of historical time-series. But then another difficulty arises. The competing hypotheses are themselves complex and subtle. We know before we start that all of them, or at least many of them, are capable of fitting the data in a gross sort of way. Then, in order to make more refined distinctions, we need long time-series observed under stationary conditions. Unfortunately, however, economics is a social science. It is subject to Damon Runyon's Law that nothing between human beings is more than three to one. To express the point more formally, much of what we observe cannot be treated as the realization of a stationary stochastic process without straining credulity. Moreover, all narrowly economic activity is embedded in a web of social institutions, customs, beliefs, and attitudes. Concrete outcomes are indubitably affected by these background factors, some of which change slowly and gradually, others erratically. As soon as time-series get long enough to offer hope of discriminating among complex hypotheses, the likelihood that they remain stationary dwindles away, and the noise level gets correspondingly high. Under these circumstances, a little cleverness and persistence can get you almost any result you want. I think that is why so few econometricians have ever been forced by the facts to abandon a firmly held belief. Indeed, some of Fortune's favorites have been known to write scores of empirical articles without once feeling obliged to report a result that contradicts their prior prejudices. If I am anywhere near right about this, the interests of scientific economics would be better served by a more modest approach. There is enough for us to do without pretending to a degree of completeness and *Department of Economics, Massachusetts Institute of Technology, Cambridge, MA 02139.